Fifteen-minute consultation on the healthy child: breast feeding. Issue 1 (28th July 2016) - Cleugh, F; Langseth, A
Abstract : Despite extensive evidence about the benefits of breast feeding for both infants and mothers, breastfeeding rates in the UK remain low. Most infants presenting with feeding issues are otherwise well but are often over diagnosed with clinical conditions such as maternal milk insufficiency, cow's milk intolerance or reflux. With simple advice and troubleshooting common problems, all child health professionals can support mothers to establish and continue breast feeding exclusively for longer.